School tourism in health resorts, exemplified by school trips organized for children and teenagers from Krakow // Turystyka szkolna w uzdrowiskach na przykładzie wycieczek szkolnych dla dzieci i młodzieży ze szkół krakowskich - Stach, Elżbieta (Geotourism/Geoturystyka, 2020)
The process of organizing school trips should include such didactic elements as teaching, education, integration and recreation, as well as take into account the principles of a healthy lifestyle associated with the renewal and regeneration of psychophysical strength. Teachers organizing such excursions should, already in the process of planning, be guided by the values, potential benefits and attractiveness of the travel destinations. Health resorts, where the local climate creates optimum conditions for relaxation, constitute important travel destinations of trips organized for children and teenagers. The purpose of this article is to present towns and villages that are classified as health resorts as a reception space, which due to the qualities of their natural and cultural environment can influence the tourist activity of primary and middle school students. School tourism in the selected health resorts has been characterized in this paper for the purpose of conducting research.//Podczas organizacji wycieczek szkolnych powinno uwzględniać się takie elementy dydaktyczno-wychowawcze jak nauczanie, wychowanie, integracja czy rekreacja, przy jednoczesnymuwzględnieniu zasad zdrowego stylu życia związanego z odnową i regeneracją sił psychofizycznych. Nauczyciele, pełniąc rolę organizatorów wycieczek, już w trakcie planowania wyjazdówpowinni kierować się walorami środowiska miejsca pobytu i jego potencjalnymi korzyściami. Ważnymi kierunkami wśród wyjazdów dzieci i młodzieży szkolnej są miejscowości uzdrowiskowe,których lokalny klimat stwarza optymalne warunki do wypoczynku. Celem artykułu jest zaprezentowanie miejscowości mających status uzdrowiska jako przestrzeni recepcyjnej, której wysokie walory środowiska przyrodniczo-kulturowego mogą wpływać na aktywność turystyczną uczniów szkół podstawowych i gimnazjalnych. Na potrzeby badań scharakteryzowano szkolny ruch turystyczny w wybranych uzdrowiskach.